Exploration of Sam Poo Kong Building Heritage as Starting Point in Geometric Transformation Course - Aisyah, Fifin; Lestari, Aidha Aprilia Puji; Supriyanto, Muhammad Agus; Nursyahidah, Farida (Mathematics Education Journal, 2022)
Sam Poo Kong is one of Semarang's city cultural heritages. This historical structure features intriguing architecture as well as being a popular tourist destination. This study aims to explore Sam Poo Kong's building as a starting point in the geometric transformation course. Besides, the study method is descriptive in qualitative terms with the ethnography approach, namely the type of research to describe and acquire data as a whole, comprehensive, and in-depth. The result is an ethnomathematics exploration of Sam Poo Kong's historic buildings, representing mathematical concepts including reflection, translation, rotation, dilation, and cultural values. Based on implementation in transformation class, students can quickly grasp which Sam Poo Kong's building portrays transformation. Students can identify and describe the Sam Poo Kong building's transformation forms, which include: 1) reflection on the temple as a whole, ornaments, and Sam Poo Kong entrance gates; 2) translation on the statues, roofs, lanterns, and poles; 3) rotation on the bedug, reliefs, incense holders, lanterns, and anchors; and 4) dilatation of the inner and outer rooflines of the Sam Poo Kong building. This can stimulate students to envisage the types of transformation, which makes the information easier to learn.Moreover, this study can benefit teachers for local wisdom context reference in geometric transformation and following researchers for further study.DOI : https://doi.org/10.22342/jpm.16.1.13073.15-28